2021
DOI: 10.1186/s13023-020-01669-1
|View full text |Cite
|
Sign up to set email alerts
|

Protein signature of human skin fibroblasts allows the study of the molecular etiology of rare neurological diseases

Abstract: Background The elucidation of pathomechanisms leading to the manifestation of rare (genetically caused) neurological diseases including neuromuscular diseases (NMD) represents an important step toward the understanding of the genesis of the respective disease and might help to define starting points for (new) therapeutic intervention concepts. However, these “discovery studies” are often limited by the availability of human biomaterial. Moreover, given that results of next-generation-sequencing… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
25
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 23 publications
(26 citation statements)
references
References 41 publications
1
25
0
Order By: Relevance
“…Indeed, our proteomic study indicated altered expression of numerous proteins decisive for proper function of the neuromuscular axis (supplementary material, Table S3). This molecular finding not only provides first insights into the biochemical origin of the broad neurological involvement of WASHC4 deficiency but also confirms the suitability of fibroblasts for identifying pathophysiological processes of neuronal relevance [15]. Along this line, these data suggest that a molecular interplay of dysregulated proteins might contribute to the clinical manifestation of symptoms.…”
supporting
confidence: 67%
See 1 more Smart Citation
“…Indeed, our proteomic study indicated altered expression of numerous proteins decisive for proper function of the neuromuscular axis (supplementary material, Table S3). This molecular finding not only provides first insights into the biochemical origin of the broad neurological involvement of WASHC4 deficiency but also confirms the suitability of fibroblasts for identifying pathophysiological processes of neuronal relevance [15]. Along this line, these data suggest that a molecular interplay of dysregulated proteins might contribute to the clinical manifestation of symptoms.…”
supporting
confidence: 67%
“…To identify proteins, which are affected by loss of functional WASHC4, proteomic profiling was carried out on skin fibroblasts derived from a WASHC4 patient. This approach was prompted by the molecular observation that a variety of proteins of neurological relevance are expressed in these cells [15]. Indeed, our proteomic study indicated altered expression of numerous proteins decisive for proper function of the neuromuscular axis (supplementary material, Table S3).…”
mentioning
confidence: 99%
“…To obtain insights into the mechanism underlying the pathophysiology of mutations in DNAJC3, unbiased proteomic studies utilizing patient-derived fibroblasts were carried out (Figure 1). While fibroblasts are not the primary site of clinical manifestation, these cell models have been previously shown to be suitable to study the etiology of rare neurological diseases (Hentschel et al, 2021) and show very similar levels of DNAJC3 expression to peripheral nerve (Supplementary Figure 1). Results of this profiling suggest that lipid metabolism is affected by DNAJC3 mut mutations (Figure 1) as Sterol-O-acyltransferase 1 (SOAT1), an enzyme responsible for the esterification of fatty acids, especially cholesterol (Das et al, 2008), was found to be decreased.…”
Section: Discussionmentioning
confidence: 99%
“…Studies on DNAJC3-silenced rat and human β cells did not affect insulin content and secretion but sensitized cells to ER stress, triggering mitochondrial apoptosis (Lytrivi et al, 2021). To further unravel this pathophysiological route here, we focused on elucidating the pathomechanism of DNAJC3-related pathology by performing proteomics in patient-derived primary fibroblasts, a suitable model to study the etiology of rare neurological diseases (Hentschel et al, 2021), and further investigation of the suggested cellular phenotype.…”
mentioning
confidence: 99%
“…A recent study indicated that the protein signature of human skin fibroblasts may help understand the pathogenic mechanisms of neuromuscular diseases [18]. We decided to study the proteome of MSS patient fibroblasts (HF-MSS) with a view to understanding the molecular changes involved in the pathogenesis of this syndrome.…”
Section: Introductionmentioning
confidence: 99%